Pre-Cycloplegic Exam Benefit of Photoscreening and Accommodation-Relaxing Skiascopy - Schaafsma JD; Arnold RW (Clinical Ophthalmology, 2024)
Jacob David Schaafsma,1 Robert W Arnold2 1School of Medicine, University of Milan, Milan, Italy; 2Alaska Blind Child Discovery, Alaska Children’s EYE & Strabismus, Anchorage, AK, USACorrespondence: Robert W Arnold, Alaska Blind Child Discovery, Alaska Children’s EYE & Strabismus, 3500 Latouche Street #280, Anchorage, AK, 99508, USA, Tel +1(907)561-1917, Fax +1(907)563-5373, Email eyedoc@alaska.netBackground: Seeking a quick way to estimate refractions for challenging pediatric patients, we studied two non-contact methods with particular attention to accuracy and level of stress in uncovering cycloplegic hyperopia.Methods: Newly referred and follow-up pediatric eye patients had timed school bus accommodation-relaxing skiascopy (SBARS) and Plusoptix A12 (Px) photoscreener testing before cyclopentolate 1% confirmatory examinations. The ABCD ellipsoid univariate method based on relative blur and vector components was used to compare dry sphero-cylinder refraction estimates with cycloplegic. Receiver operating characteristic (ROC) curves were used to determine screening value.Results: Three compared refractions were attempted in 191 racially diverse children of whom 100 were age 0.2– 3.9 years and 91 were 4 to 14 years. Plusoptix failed to yield a result in 21 and an additional 21 were interpreted as an excess sphere. Median spherical equivalent did not differ between Px and SBARS for 149 with Px readings but in hyperopic patients, Plusoptix uncovered 27% less hyperopia. The ellipsoid for SBARS of 0.8 was better than 2.4 for Plusoptix (Mann–Whitney p< 0.001). Plusoptix was fastest (3– 15 seconds) followed by SBARS (15– 30 seconds) compared to 30– 45 minutes for cycloplegic exam.Conclusion: Non-contact quick refractive methods enhanced confirmatory cycloplegic pediatric exam in high-risk pediatric patients.Keywords: sphero-cylinder, refraction, autorefraction, photoscreening, developmental delay